THE SIGNIFICANCE OF EXPERIENCE OF WEST BENGAL FOR POVERTY ALLEVIATION IN BANGLADESH - A. A. Nemova (Vestnik MGIMO-Universiteta, 2017)
The article analyzes socio-economic problems and ways of eliminating poverty in Bangladesh. The focal point of the research is poverty among rural population which is the most vulnerable one. The author’s assumption is that the main reason for rural poverty is historical inequality of land property distribution in Bangladesh. The existing measures of poverty alleviation in Bangladesh (micro crediting among others) have made the country a role model for development. However, due to the limited potential of micro crediting a broader program of socio-economic reforms is required for any country striving to provide inclusive development. Using comparative-historical method the article compares the experience of Bangladesh and Indian state of West Bengal in implementing agricultural reforms aimed at improving life of the poor. West Bengal under the CPM rule is considered as a state with strong government whereas Bangladesh is considered as a state with weak government but rather strong non-governmental actors (NGOs). The article makes a conclusion that a weak institutional power of Bangladesh is one of the main reasons why agricultural reforms have not been adopted in this country and that poverty elimination there requires structural reforms to redistribute land property and to guarantee rural population legal and economic equality.